PANDEMI CORONA VIRUS (COVID 19) DALAM PERSPEKTIF BUDAYA LAMAHOLOT-FLORES TIMUR - Yosef Masan Toron (Jurnal Alternatif Wacana Ilmiah Interkultural, 2022)
COVID -19 has been known as the most dangerous disease for human being. The COVID -19 virus started in Wuhan, China, at the end of 2019, and in short time became the health world wide issue. There are no countries in the world that are not influenced by such issue. Governments in different countries, including Indonesia have been triying to make different programmes to cope the issue. But until now, the issue about COVID -19 is still going on. The issue of COVID 19 for most of tribes in Indonesia is not merely a health issue. It is also understood as a socio-religiuos issue. The issue of COVID -19 has a close relationship with their faith on existence of the High Beeing, the spirits and ancestor . They do believe that all realities in the world comes into existence because of the power of God, guided by different spirits and ancestor. In such perspective of faith, different problems and black experiences including different kind of diseases are understood as the punishment of the High Beeing. Human being who come into existence by the creative power of the High Beeing, are supposed not faithfull enough in following the will of the High Beeing, the spirits and ancestor. Based on this religius faith, the High Beeing, the spirits and the ancestor must be invited and get involved in any inisitive to solve the problems. The Corona Virus 19 has become a very crucial experience for human being in all over the world. Facing such issue, the people of Lamaholot, who live in estern part of Flores Island, has practised different rites to overcome the issue. They do believe that by doing such rite in different places, they could make a kind of reconciliation with the High Beeing, the spirits and the ancestor that could make them free from all kind of the punishments.